The aggregate stability of the soil in respect to the uniform aggregate stability indicator - Huisz, Andrea (Acta Agraria Debreceniensis, 2007)
Soil structure and its quality are fundamental properties because they control many processes in soils. Tillage, crop and other factors influence soil structure. Efficient protection of it needs indication of changes in soil structure. A new Normalized Stability Index proposed by Six et al. (2000) tries to evaluate these changes, which was compared with some former used indices. The most common method (wet sieving) was modified to reduce the confounding effects of different particle size distribution of different soil types and method used to the investigation. Changes in soil structure caused by tillage and crop management therefore have been made quantitative and comparable. In this paper, we review the new method and Normalized Stability Index proposed by Six et al. (2000) and present the results of our investigations.